Ecocriticism and Sacred Space in Raja Alem’s The Dove’s Necklace: Urban Transformation and Cultural Displacement in Mecca - Al-Ghamdi, Kholoud (International Journal of Language and Literary Studies, 2025)
This study analyzes The Dove’s Necklace by Raja Alem from an ecocritical perspective, focusing on the novel’s depiction of the dynamic, often antagonistic, relationships between modernity, cultural memory, and environmental conflict in Mecca. The novel’s critique of cultural and ecological consequences of development is set amidst rapid changes to the urban fabric of the Saudi state as per Vision 2030. The problem addressed in this research relates to the scant attention given to ecocriticism within contemporary Saudi literature, most especially literature that deals with sacred urban spaces. The study is qualitative in nature. It uses thematic and textual analysis within the framework of five interconnected ecocritical themes to analyze urbanization and environmental degradation, the conflict of modernity and tradition, the significance of the natural world in cultural and spiritual identity, the human-nature dynamic, and the environmental degradation and loss in the personal and collective psyche. The ecological and cultural disruption is demonstrated by the literary figures of the vanished doves, the lost deserts of the ancestors, and the streets of Mecca. This study contributes to the field of ecocriticism, especially for non-Western scholars, by juxtaposing Western scholarship on ecocriticism and Islamic environmental ethics. The study provides evidence of literature’s ability to articulate urban change’s impact on cultural discontinuity and addresses issues of interest to researchers, teachers, and policymakers on the intersections of urban development, cultural sustainability, and then, of course, literature.